Evaluation of Online Learning During the Covid 19 Pandemic - I Gusti Agung Ayu Wulandari; I Wayan Suastra; Ida Bagus Putu Arnyana (Jurnal Ilmiah Sekolah Dasar, 2022)
Learning that is usually done face-to-face has turned into virtual face-to-face learning. This certainly raises various problems, including theaspect context concerning government policies in the field of education, theaspect input relating to online learning supporting infrastructure, the process aspect concerning the readiness of educators to conduct online learning, and theaspect product relating to student learning outcomes. Therefore, this research is very urgent to find out whether or not the implementation of online learning from the previously mentioned CIPP component is effective. It is important to do this as an evaluation material that the government can do regarding learning during the covid 19 pandemic. This research is an evaluation study using the CIPP (Context, Input, Process, Product) evaluation model. The subjects studied in this study were 698 people from the total population of 3,334. The method of data collection in this study, using the non-test method by distributing closed questionnaires. Data were analyzed using quantitative descriptive statistics, then converted into Z scores and transformed into T scores. Based on the data analysis, the results showed that  the components of the context variable were effective, the input variables were less effective, the process variables were effective and the product variables were effective, so it can be concluded that the implementation of online learning is in quadrant II (second) or quite effective. Recommendations for further research are that it is necessary to improve indicators that have not been running well/effectively and to find solutions to various obstacles in online learning, so that the quality of online learning increases.